KAJIAN SISTEM PEMANTAUAN PEREDARAN KAYU BUNDAR - Triyono P; Hariyatno D P (Pusat Penelitian dan Pengembangan Hasil Hutan, 1996)
The change of assessing reforestation fund (DR) and forest product fee (IHH) on logs from official assessment lo self assessment by forest concession holder also changed the supervision of logs flow. The aim of this study is; 1) lo compare the difference between old system and new system and 2) lo see how the new system of supervising as it operates in the field can be improved.The study which was analysed using quantitative and qualitative approach showed that despite of its disadvantage, self assessment has some advantages with respect 10 flows of logs because of simpler log administrative procedure. However, it decreased goverment revenue because of illegal logs and the delay in DR payment. The new system can be refined by improving the coordination and communication among forestry offices so the log flow can bebetter supervised.Key word : reforestation fund, forest product fee, logs flow, official assessment, self assessment.